Crushing Behaviour of Filled Tubes Under Static and Dynamic Loading Conditions: A Review - Nurul Izzah, Ab Rahim; Salwani, Mohd Salleh; Mohd Shahril, M. (Science Publishing Corporation, 2018)
Crash box structure is one of the safety requirement that should be considered in vehicle design to ensure safety of the passengers. This paper was developed to summarize the simulation and experimental study that have been conducted regarding the energy absorption capability of a thin-walled tubes. The energy absorption structure can be made of metal or composite thin-walled tubes with variety configurations. These thin-walled structures were filled with foams, honeycomb or composite to enhance the energy absorption capability. A few types of foam-filled and honeycomb-filled with addition of composite to enhance the energy absorption were discussed in this paper. Trigger mechanism with foam-filled was also introduced to increase the energy absorption and protect the passenger during collision. Functionally graded thickness of wall and functionally graded density of foam were introduced in form of simulation study to investigate the effect of the graded configuration to energy absorption capability. In author’s opinion, the most promising or more advantages filler among all that have been discussed is functionally graded foam which was recently the investigated using finite element simulation.